Identification of novel ALK rearrangement A2M–ALK in a neonate with fetal lung interstitial tumor. Issue 10 (26th June 2014) - Onoda, Tadashi; Kanno, Miyako; Sato, Hiroko; Takahashi, Noriyuki; Izumino, Hiroko; Ohta, Hiroshi; Emura, Takaki; Katoh, Hirohisa; Ohizumi, Hiroyuki; Ohtake, Hiroya; Asao, Hironobu; Dehner, Louis P.; et al.
<x xml:space="preserve">Abstract</x> Fetal lung interstitial tumor (FLIT) is a recently reported type of congenital lung lesion comprising solid and cystic components. The pathological features include unique interstitial mesenchyme‐based cell proliferation, and differ from other neoplasms represented by pleuropulmonary blastoma or congenital peribronchial myofibroblastic tumor. FLIT is extremely rare and its gene expression profile has not yet been reported. We provide the first report of a novel chromosomal rearrangement resulting in α‐2‐macroglobulin (A2M) and anaplastic lymphoma kinase (ALK) gene fusion in a patient with FLIT. The tumor cells contained a t(2;12)(p23;p13) and were mesenchymal in origin (e.g., inflammatory myofibroblastic tumors), suggesting the involvement of ALK in this case of FLIT. Break apart fluorescence in situ hybridization demonstrated chromosomal rearrangement at ALK 2p23. Using 5′‐rapid amplification of cDNA ends, we further identified a novel transcript fusing exon 22 of A2M to exon 19 of ALK, which was confirmed by reverse‐transcription polymerase chain reaction. The corresponding chimeric gene was subsequently confirmed by sequencing, including the genomic break point between intron 22 and 18 of A2M and ALK, respectively. Discovery of A2M as a novel ALK fusion partner, together with the involvement of ALK, provides new insights into the pathogenesis of FLIT, and suggests the potential for new therapeutic strategies based on ALK inhibitors. © 2014 Wiley Periodicals, Inc.